2014
DOI: 10.4025/actascianimsci.v36i3.21834
|View full text |Cite
|
Sign up to set email alerts
|

<b>Inclusion of leucaena leaf hay in the diet of laying hens during the growing phase

Abstract: ABSTRACT. Current experiment evaluated the effects of inclusion of leucaena leaf hay (LLH) on the performance and nutrient digestibility of diets for laying hens during the growth phase (14-18 weeks). Ninety pullets (Rhode Island Red and New Hampshire) were distributed in a completely randomized design with three treatments (0%, 5% and 10% inclusion of LLH) and five replicates, with six birds. Feed intake (g bird -1 day -1 ), weight gain (g bird -1 day -1 ), feed conversion (kg kg -1 ), metabolizable energy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Ayssiwede et al (2010) did not identify a reduction in FI with the levels of 0, 7, 14 and 21% of LLM in adult chickens. Oliveira et al (2014) showed no influence of 0, 5 and 10% LLM on FI in laying hens at the growing phase. In contrast with our results, Lopes et al ( 2014) identified a higher FI in laying hens fed with corn-and sorghum-based diets with 2% FFL.…”
Section: Seminamentioning
confidence: 78%
See 1 more Smart Citation
“…Ayssiwede et al (2010) did not identify a reduction in FI with the levels of 0, 7, 14 and 21% of LLM in adult chickens. Oliveira et al (2014) showed no influence of 0, 5 and 10% LLM on FI in laying hens at the growing phase. In contrast with our results, Lopes et al ( 2014) identified a higher FI in laying hens fed with corn-and sorghum-based diets with 2% FFL.…”
Section: Seminamentioning
confidence: 78%
“…Although Leucaena it is a plant rich in nutrients, it contains tannins, trypsin inhibitors and toxic substances, such as the non-protein amino acid β-[N-(3-hydroxy-4oxo pyridyl)]-α-aminopropionic (mimosine); its fibre level restricts its use by affecting the performance of laying hens according to the inclusion levels (Dumorné, 2018;Oliveira et al 2014).…”
Section: Sorghummentioning
confidence: 99%
“…Increasing fiber level in the diet may cause several metabolic and physiological effects in the broiler organism such as increase in the rate of endogenous excretion, and reduction in the activity of digestion enzymes and of the feed pathway through the gastrointestinal tract (Araujo & Silva, 2008; Nunes De Oliviera et al, 2014). Shaddel‐Tili, Eshratkhah, Kouzehgari, and Ghasemi‐Sadabadi (2017) have reported that the process of absorption that occurs in the body of the livestock is influenced by the age, so that the feed given to livestock should be adjusted to the age.…”
Section: Discussionmentioning
confidence: 99%
“…However, the production of adequate food is the biggest challenge for industries (Cullere et al., 2017). Many investigations have been conducted to evaluate the suitability of various feed ingredients as alternative protein and energy sources for poultry (Abdel‐Hafeez Saleh, Tawfeek, Youssef, & Abdel‐Daim, 2018; Azizi et al., 2018; Ebrahimi, Qotbi, Seidavi, Laudadio, & Tufarelli, 2013; Gatrell, Derksen, O’Neil, & Lei, 2017; Nunes De Oliviera, Freitas‐Braga, Thales, Jeromino Do Nascimiento, & Castro‐Lima, 2014). However, scarce interest has been given to banana flour as potential ingredient for poultry diets.…”
Section: Introductionmentioning
confidence: 99%
“…However, green forages contain more fiber and less energy and feeding of excessive forages may depress performance [Horsted et al, ]. There are some studies which indicate that small amounts of green forages can be incorporated into layer diets without any adverse effect on performance [Odunsi et al, ; Kakengi et al, ; Oliveira et al, ]. It is well documented that there is inter‐species difference in feed consumption and nutrient utilization among different species of bird [Sultan et al, ; Sheppard et al, ].…”
Section: Introductionmentioning
confidence: 99%